التّجليات الجماليّة للقبيح في قصص زكريّا تامر السّلطة أنموذجاً - بركات, عبير; إسماعيل, هناء (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
وقع اختياري على هذا البحث، لأنّه لم يأخذ حقّه في حقل الدراسات النقديّة الأدبيّة كما ينبغي، إذ اهتمّت هذه الدراسات بالبعد الإيديولوجي للسلطة أكثر من اهتمامها ببعده الفني، رغم ما تكشفه القصص ذات الطابع السلطوي من براعة القاصّ في تطويع المادّة القصصيّة لإمكاناته التعبيريّة الخلاقة، وهو ما نهدف إلى إضاءته في هذا البحث، وذلك بالنظر إلى دور الفنّ في إعادة إنتاج المشكلات الأخلاقيّة بوعي أكثر استبصاراً بالواقع ممّا قد تقدّمه القراءات الإيديولوجيّة المختلفة، إذ إنّ التمثيل الجمالي للقبيح السلطوي يكشف عن الفجوة الهائلة بين عالمين لا ينتمي أحدهما إلى الآخر، عالم من يملك القرار ومصائر الناس، وعالم من لا يجد أمامه سوى الخوف والرعب والكوابيس. ومن هنا جاء تركيزنا على دور الكلمة السلطويّة في الإشارة إلى هرطقة السلطة، ولا جدوى الحوار معها، إضافة إلى دور الوصفين الواقعي والمجازي في الإشارة إلى سيكولوجيا السلطة وجاهزيّتها الدائمة لتدمير الذات الإنسانيّة، متكئين في ذلك على المنهج الجمالي، مع الاستفادة ممّا تقدّمه المناهج الأخرى من رفد لهذه الدراسة. I have chosen this topic because it has not been properly tackled in the field of literary critical studies. These studies have rather focused on the ideological dimension of the power theme rather than on its technical aspect despite the fact that stories of authoritarian nature reveal the skill of the short-story writer in manipulating the narrative material to serve his creative capabilities. This research focuses on the importance of art in reproducing the ethical problems with an awareness that fathoms reality more efficiently than is rendered by various ideological readings. The aesthetic representation of the authoritarian ugly reveals the great gap between two worlds wide apart: the world of those in whose hands laid decision- making and problem's destiny, and that of those who live under fear and nightmares. This is why we focus on the role of the authoritarian word in pointing to the heresy of the authority and the futility of opening a dialogue with it, together with the role of the real and metaphorical descriptions in pointing to the psychology of power and its constant readiness to annihilate the human entity. In so doing, we rely on the aesthetic approach making use, too, of what the other approaches may yield to this study.